2006
DOI: 10.1002/ajmg.a.31193
|View full text |Cite
|
Sign up to set email alerts
|

CHARGE syndrome: Relations between behavioral characteristics and medical conditions

Abstract: The behaviors and medical problems in 27 persons with CHARGE syndrome were studied, because it was hypothesized that their behavior might be partly dependent on the heterogeneous medical status. With the exception of more tics, cardiac surgery was associated with positive behaviors: less withdrawn behavior, better mood, and a more easy temperament. Tube feeding was also related to positive behavior, since participants with a history of tube feeding showed less intense behavior. Cerebral deficits were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…As mentioned by Blake et al ( 2005 ) and Vervloed et al ( 2006 ), it is difficult to describe the typical CHARGE person because the characteristics are so highly variable. Our sample was also heterogeneous with regard to physical and behavioral problems, for example only 13% of the measured behavioral problems were exhibited by more than half of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned by Blake et al ( 2005 ) and Vervloed et al ( 2006 ), it is difficult to describe the typical CHARGE person because the characteristics are so highly variable. Our sample was also heterogeneous with regard to physical and behavioral problems, for example only 13% of the measured behavioral problems were exhibited by more than half of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with CHARGE syndrome vary widely in the combination of physical problems present as well as their level of functioning and behavioral characteristics (Blake et al 2005 ; Vervloed et al 2006 ). The level of functioning ranges from profound intellectual disability (ID) to normal intelligence, but a substantial proportion seem to function in the lower range (Johansson et al 2006 ; Salem-Hartshorne and Jacob 2005 ; Smith et al 2005 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that GERD, combined with feeding and breathing difficulties, was a significant risk factor for early mortality in CHARGE syndrome (Bergman et al, 2010). Esophageal reflux has also been shown to be a significant predictor of longer hospital stays in this genetic disorder (Vervloed, Hoevenaars-van den Boom, van Ravenswaaij, & Ronald Admiraal, 2006 fundoplication failure has been found to be herniation into the posterior mediastinum. Even after surgery, many continue to need medical management of symptoms.…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…We consider this a possible comorbid condition in a few cases, but not useful as a diagnostic criterion given the difficulty of diagnosing autism in the presence of poor sensory integration and lack of sensory input in individuals with deaf‐blindness. Further, the literature suggests that behaviors presented in CHARGE syndrome are indicative of multiple sensory impairments and not ASD [Vervloed et al, ]. While some of the stereotyped behaviors individuals with CHARGE syndrome engage in are similar to those in children with ASD (i.e., rocking, eye pressing/poking, spinning, jumping, gazing), the function of these behaviors for individuals with CHARGE syndrome may be better explained by the visual/hearing impairments and other sensory related deficits they experience and must compensate for [Fazzi et al, ; Johanasson et al, ].…”
Section: To the Editormentioning
confidence: 99%